2007
DOI: 10.1007/s11661-006-9076-3
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observations of Sigma Phase Formation in Duplex Stainless Steels Using In-Situ Synchrotron X-Ray Diffraction

Abstract: The formation and growth of sigma (σ) phase in 2205 duplex stainless steel was observed and measured in real time using synchrotron radiation during 10 hr isothermal heat treatments at temperatures between 700ºC and 850ºC. Sigma formed in near-equilibrium quantities during the isothermal holds, starting from a microstructure which contained a balanced mixture of metastable ferrite and austenite. In situ synchrotron diffraction continuously monitored the transformation, and these results were compared to those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
1
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(95 citation statements)
references
References 28 publications
7
77
1
10
Order By: Relevance
“…The kinetics of sigma formation measured in this study is consistent with that reported by Magnabosco 4 and with the results of Elmer et al 2 obtained using In-situ Synchrotron X-Ray Diffraction. More important than the kinetic measurements, however, is the indication that the Barkhausen noise signal can be adequately used to assess the decrease in ferromagnetic phase over time, thus making it a valuable non-destructive technique.…”
Section: Barkhausen Noise Measurementssupporting
confidence: 93%
See 1 more Smart Citation
“…The kinetics of sigma formation measured in this study is consistent with that reported by Magnabosco 4 and with the results of Elmer et al 2 obtained using In-situ Synchrotron X-Ray Diffraction. More important than the kinetic measurements, however, is the indication that the Barkhausen noise signal can be adequately used to assess the decrease in ferromagnetic phase over time, thus making it a valuable non-destructive technique.…”
Section: Barkhausen Noise Measurementssupporting
confidence: 93%
“…Since σ is the intermetallic phase more prominently formed during field applications of duplex stainless steel, its formation has been the object of several studies throughout the years, mostly focused on morphology and formation kinetics [1][2][3][4][5][6][7][8] , as well as its effects on mechanical properties [9][10][11] and corrosion resistance [12][13][14][15][16][17] . Processes that include high temperature thermal cycling, such as welding, are particularly critical regarding the appearance of σ, due to the temperature range to which the heat affected zone is exposed in a poorly controlled manner.…”
Section: Introductionmentioning
confidence: 99%
“…The in-situ x-ray diffraction was performed while heating test coupons in vacuum (10 -4 Torr) using a direct resistance method [15][16][17]. The heating cycle consisted of a 20ºC/sec ramp to the initial temperature of 850ºC where it was held for 30 min to form a measurable amount of sigma.…”
Section: In-situ X-ray Diffraction Experiments and Datamentioning
confidence: 99%
“…Additional details about the data acquisition technique on this beam line are presented elsewhere [15][16][17]. Figure 4 shows a room temperature diffraction pattern (upper line) taken after an 850ºC heat treatment where a significant amount of sigma phase had formed [7].…”
Section: In-situ X-ray Diffraction Experiments and Datamentioning
confidence: 99%
“…Sigma phase reduces the elongation and toughness too, although it increases hardness, yield point and tensile strength in the matrix. Precipitation of 1% of this phase reduces by 50% the initial value of the absorbed energy in the Charpy test 11,12 .…”
Section: Introductionmentioning
confidence: 98%